Rectifier transformers in electric traction substations – different designs - Kulesz, Barbara (Transport, 2005)
Electric traction in Poland is supplied with dc voltage which is obtained from the power grid via traction substations equipped with transformers and rectifiers. The paper gives the results of the investigation of different designs of these transformer‐rectfier sets – namely, 12‐ and 24‐pulse systems. The comparison of electrical quantities such as ripple content, harmonic content of supply current and output voltage and utilisation of transformer secondary windings is provided. First Published Online: 27 Oct 2010